2016
DOI: 10.1007/s11999-016-4821-4
|View full text |Cite
|
Sign up to set email alerts
|

Will My Tibial Fracture Heal? Predicting Nonunion at the Time of Definitive Fixation Based on Commonly Available Variables

Abstract: Background Accurate prediction of tibial nonunions has eluded researchers. Reliably predicting tibial nonunions at the time of fixation could change management strategies and stimulate further research. Questions/purposes We asked (1) whether data from medical records, fracture characteristics, and radiographs obtained at the time of fixation would identify features predictive of tibial fracture nonunion; and (2) whether this information could be used to create a model to assess the chance of nonunion at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 43 publications
2
56
0
1
Order By: Relevance
“…As with all these complex disease patterns, the study cohort was heterogeneous, making it difficult to control possible confounding factors. Westgeet et al 41 Journal of Orthopaedic Surgery 25 (2) et al 42 showed that AO classification (odd ratio (OR) 1.86), gunshot wounds (GSW) (OR 1.98), fracture location and pattern (OR 0.46-1.36), open fractures (OR 3.9), smoking (OR 1.8), EtOH use (OR 1.6), HIV (OR 4), NSAID use (OR 1.5), diabetes (OR 2.2), compartment syndrome (OR 4), vascular injury (OR 2), muscle flap (9.6), and deep infection (OR 12.75) were variables that potentially influences union. However, it can be assumed that all factors with the exception of muscle flap soft-tissue cover (100% in the tibial fracture group, 58% in the infected nonunion group) and deep infection (0% in the tibial fracture group and 100% in the infected nonunion group) were equally distributed within the two groups and did not influence the results greatly.…”
Section: Discussionmentioning
confidence: 99%
“…As with all these complex disease patterns, the study cohort was heterogeneous, making it difficult to control possible confounding factors. Westgeet et al 41 Journal of Orthopaedic Surgery 25 (2) et al 42 showed that AO classification (odd ratio (OR) 1.86), gunshot wounds (GSW) (OR 1.98), fracture location and pattern (OR 0.46-1.36), open fractures (OR 3.9), smoking (OR 1.8), EtOH use (OR 1.6), HIV (OR 4), NSAID use (OR 1.5), diabetes (OR 2.2), compartment syndrome (OR 4), vascular injury (OR 2), muscle flap (9.6), and deep infection (OR 12.75) were variables that potentially influences union. However, it can be assumed that all factors with the exception of muscle flap soft-tissue cover (100% in the tibial fracture group, 58% in the infected nonunion group) and deep infection (0% in the tibial fracture group and 100% in the infected nonunion group) were equally distributed within the two groups and did not influence the results greatly.…”
Section: Discussionmentioning
confidence: 99%
“…This limits its use to fractures with a cortical displacement. However, a lack of cortical continuity on radiographs after operative fixation is presumed to be a risk factor for the development of a non-union [9,11,13]. In these cases, CEUS could support accurate determination of the consolidation status towards an early detection of failed fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial non-unions mainly affect patients at the age of 30-44 years [14]. The potential long-term disability can result in manifold socioeconomic problems [10,11]. Thus, early diagnosis and correct classification are of utmost importance in order to optimize treatment and to minimize subsequent disability [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The RUST approach has demonstrable intra-and inter-observer reliability (Leow et al, 2016;Whelan et al, 2010), has been adapted for use in metaphyseal fractures (Litrenta et al, 2015), and has become a commonly used tool in the design of randomized controlled trials (Castillo et al, 2017). The advantage of RUST scoring is that it was designed to capture the development of external callus at the fracture site and has demonstrated utility as a tool to differentiate between united and nonunited fractures (RUST > 10 for union) in clinical studies (Bishop et al, 2012;O'Halloran et al, 2016;Van Houten et al, 2014). However, RUST scores are not objective and interpretation of the scoring criteria can be ambiguous, leading to known difficulties in inter-rater agreement (Leow et al, 2016).…”
Section: Introductionmentioning
confidence: 99%